Optimalisasi Line Balancing Menggunakan Metode Ranked Positional Weight, Moodie Young, dan J-Wagon - Yetrina, Mutiara; Fitri, Meldia; Susriyati; Laurenza, Soviana (Universitas Putra Indonesia YPTK Padang, 2023)
CV. Cahaya Furniture is an industry engaged in Furniture, which is located in Kampung Jua, Lubuk Begalung Nan XX District. In the teak cupboard production process, there is an imbalance in the teak cupboard production. This study aims to deterine the performance of the production line balance using the Ranked Positional Weight, Moodie Young, and J-Wagon methods. The results show that the current track efficiency is 76.83%, Balance Delay is 32.17%, Smoothness Index is 36.13 with 5 work stations, whereas after calculating with the Line Balancing method, the result is that using the Ranked Positional Weight method the increased efficiency value increased to 96.04%, the balance delay decreased to 3.96%, the smoothness index was 5.32 with withdrawals being 4 work stations. In the Moodie Young method, the recovery efficiency value is the same as the initial condition, which is 76.83%, the balance delay is 23.17%, the smoothness index is 14.39 with 5 work stations. In the J-Wagon method, the track efficiency value decreased to 64.03%, the balance delay increased to 35.97%, the smoothness index was 19.65 with 6 work stations. The results of this study indicate that the most effective method used is the Ranked Positional Weight method because there is a reduction in work stations to 4, and increases transfer efficiency to 96,04%, decreases balance delay from 3.96%, and smoothness index decreases to 5.32.